Comparación de auralizaciones dinámicas generadas a partir de respuestas al impulso medidas y simuladas (2016)
Auralization is a method that allows to create sounds that represent the acoustic characteristics of specific a room, bringing the listener to a sensation of immersion. This project, seeks to compare the dynamic auralization created by measuring the room impulse response, with those created by means of the acoustical prediction software Catt-Acoustic, both of them reproduced in an OPSODIS system. As a first step, binaural impulse response at discrete points in a semi-circle in the classroom 402E of the University of San Buenaventura, Medellin, San Benito building, were measured. Secondly, the auralizations were obtained by convolving these impulse responses with audio material recorded in a "semi-anechoic" way for each of the measured points. An Catt-Acoustic model was then obtained, it was calibrated regarding the measurements through the objective comparison of the acoustic parameters EDT, T30, C80 and IACC. It was then simulated and auralizations were created. These audio files were processed in Matlab, they were fragmented by different spatial resolutions, and concatenated so that each fragment representing a position on the path to create the sensation of movement of the receiver. These dynamics auralizations were evaluated by a critical listening test and the results showed no significative differences between auralizations with different spatial resolutions, i.e. there is no difference in the sensation of continuity in the movement for the living and the path set. Grupo de Investigación: Modelamiento y Simulación Computacional. -- Línea de Investigación: Acústica y Procesamiento de Señales.